Minimizing Exposure to Ionizing Radiation in Catheter-Based Treatment of Atrial Fibrillation: Safety and Efficacy - Perepeka, Eugene O.; Kravchuk, Borys B.; Sychyk, Maryna M.; Mykolaichuk, Svitlana L. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Pulmonary vein isolation using radiofrequency ablation is the most common method of catheter treatment for atrial fibrillation. Performing this procedure involves the use of X-ray radiation, which at certain stages of the procedure is an indispensable method for navigation and visualization of intracardiac structures. Approaches to minimize X-ray exposure during catheter interventions are attracting increased attention of the electrophysiology community due to the potential risks of adverse effects of ionizing radiation on patients and medical personnel. The aim. To evaluate the effectiveness and safety of performing the pulmonary vein isolation procedure with the intention to minimize X-ray exposure of patients and medical personnel. Materials and methods. Forty-three patients with various forms of atrial fibrillation were selected for the study: 28(65%) with paroxysmal and 15 (35%) with persistent forms. All the patients underwent pulmonary vein isolation usingcatheter radiofrequency ablation with the intention to minimize X-ray exposure at the National Amosov Institute of Cardiovascular Surgery in the period from June 2023 to April 2024. Results. In all 43 patients it was possible to electrically isolate all the veins. Catheter ablation of the cavotricuspidisthmus was performed in 5 (31.2%) patients from group A (“Zero-fluoro”), 7 (33.3%) from group B (“Near Zero-fluoro”) and 3 (50%) from group C (“Non Zero-fluoro”) (p = 0.696). Intraoperative reconnection of the pulmonary veins with the left atrium was observed in 6 (37.5%) patients of group A, 11 (52.3%) of group B, and 4 (66%) of group C (p = 0.429). X-ray time for transseptal puncture did not differ between groups A and B (3.56 ± 2.37 vs. 3.69 ± 2.3 min., p = 0.532), however, X-ray time for pulmonary vein isolation in group A was significantly less than that in group B (0.27 ± 0.13 vs. 1.96 ± 1.21 min., p < 0.001). The total time in the left atrium was not statistically different between these two groups (81.33 ± 22.32 vs. 98.6 ± 29.83 min., p = 0.106). In group C (“Non Zero-fluoro”), the aforementioned parameters were not recorded. Total dose area product (DAP) and total radiation dose, as well as total X-ray time and total procedure time, were significantly lower when using the ionizing exposure minimization approach. DAP and total radiation dose in group A were the lowest (7.29 ± 5.16 Gy/cm2 and 76.62 ± 70.82 mGy, respectively) and significantly differed from those in group C (107.67 ± 97.59 Gy/cm2 and 882.32 ± 868.62 mGy, p < 0.001 and p = 0.001, respectively). No intraoperative complications were observed in the studied sample. Conclusions. Minimizing X-ray exposure using modern navigation systems during pulmonary vein isolation using catheter radiofrequency ablation is not associated with increased intraprocedural complications in patients with paroxysmal and persistent atrial fibrillation. This approach allows you to significantly lower total DAP and the radiation dosewithout increasing the time of performing the pulmonary vein isolation procedure.